An Original Monograph About Problems of the Development of the Lithuanian Auditing System - Mackevičius, Jonas (Ekonomika, 2008)
Auditing plays a very important role in economics. The fast economic development, global economic integration, increasing competition in every sphere of life greatly influence auditing.Prof. Vaclovas Lakis’ monograph “Auditing System: Problems and Development” discusses all types of auditing: independent audit, state audit and internal audit, which are discussed as a sustainable system because all of them are closely interrelated. Lithuania overtook the auditing septum, organization and ways of performing it from other countries together with their advantages and disadvantages. Therefore, the monograph investigates problems characteristic of the world auditing system. The monograph is particularly helpful for external and internal auditors, accountants, enterprise managers, teachers and university students.